2019
DOI: 10.1111/jopy.12493
|View full text |Cite
|
Sign up to set email alerts
|

Predicting trait emotional intelligence from HEXACO personality: Domains, facets, and the general factor of personality

Abstract: Objective The current study provides a comprehensive analysis of the overlap between trait emotional intelligence (EI) and personality. This overlap was examined using the HEXACO personality framework at both the domain and the facet levels, and through varying methods of deriving a general factor of personality (GFP). Method A sample of 1,370 Australian adults (51% male, age in years M = 45.5, SD = 11.7, range: 21–71) completed the 200‐item HEXACO Personality Inventory‐Revised and the Modified Assessing Emoti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Furthermore, no single Big Five domain explained more than 20% of the variance in general risk-taking, which suggests that risk-taking propensity does not neatly fall under any single existing Big Five domain. Comparatively, Anglim et al (2019) found that extraversion alone explained 44% of the variance in emotional intelligence. Taken together, our findings suggest that general risk-taking is a relatively unique construct that may be better conceptualized as a compound trait consisting of multiple Big Five components (Credé et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, no single Big Five domain explained more than 20% of the variance in general risk-taking, which suggests that risk-taking propensity does not neatly fall under any single existing Big Five domain. Comparatively, Anglim et al (2019) found that extraversion alone explained 44% of the variance in emotional intelligence. Taken together, our findings suggest that general risk-taking is a relatively unique construct that may be better conceptualized as a compound trait consisting of multiple Big Five components (Credé et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, no single Big Five domain explained more than 20% of the variance in general risk-taking, which suggests that risk-taking propensity does not neatly fall under any single existing Big Five domain. Comparatively, Anglim, Morse, Dunlop, Minbashian, and Marty, (2019) found that extraversion alone explained 44% of the variance in emotional intelligence. Taken together, our findings suggest that general risk-taking is a relatively unique construct and may be better conceptualized as a compound trait that consists of multiple Big Five components (Credé et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…The alternative concept of EI considers EI to be a set of affected-related personality traits like assertiveness, adaptability, empathy (Anglim et al, 2020;Pérez et al, 2005). According to this concept, EI is defined as "a constellation of emotion-related self-perceptions and dispositions located at the lower levels of personality hierarchies" (Petrides et al, 2007, p. 26).…”
Section: Literature Reviewmentioning
confidence: 99%